Formulation and Antibacterial Evaluation of Ethanolic Garlic Peel Emulgel Against Staphylococcus aureus and Propionibacterium acnes - Michrun Nisa; Sukriani Kursia; Rahmah Mustarin; Zulfiah Zulfiah; Wiranda Karmianti (Tropical Biopharmaca Research Center, IPB University, 2026)
Garlic peel (Allium sativum L.) is a household waste that contains bioactive compounds with potential antibacterial activity. This study aimed to formulate an emulgel containing ethanolic garlic peel extract and evaluate its physical characteristics and antibacterial activity against Staphylococcus aureus and Propionibacterium acnes. The emulgel was evaluated for organoleptic properties, homogeneity, pH, and viscosity. Antibacterial activity was tested using the agar diffusion method. The formulation showed acceptable physical characteristics for topical use. The emulgel inhibited the growth of both bacteria, with inhibition zones of 12.16 mm against S. aureus and 11.02 mm against P. acnes. The antibacterial activity may be related to the presence of flavonoids, saponins, phenolic compounds, and allicin in garlic peel extract. These results suggest that garlic peel extract can be formulated into an emulgel with potential antibacterial activity.